CLINICO - HISTOPATHOLOGICAL SPECTRUM OF CUTANEOUS VASCULITIS: A RETROSPECTIVE STUDY OF 62 CASES - Shirazi, Nadia; Jindal, Rashmi; Tyagi, Neha; Roy, Samarjit; Harsh, Meena; Ahmad, Sohaib (International Journal of Clinical and Biomedical Research, 2015)
Context: Cutaneous Vasculitis is the inflammation of vessel walls which leads to hemorrhagic or ischemic events. The histopathological classification of cutaneous vasculitis depends on the vessel size and the dominant immune cell mediating the inflammation. Object: We studied the etiological factors and clinico-pathological spectrum of patients with cutaneous vasculitis at a tertiary referral centre of north India. Design: Skin biopsies of all patients with clinically suspected cutaneous vasculitis presenting over 5 years, between 2009-2014 were reviewed. Cutaneous vasculitis was classified on the basis of etiology (primary or secondary), on the basis of size of vessel wall as well as on the dominant inflammatory cell infiltrating the vessels. Results: Over 5 years, 62 / 103 patients evaluated for vasculitic syndromes had histologically proven vasculitis. Clinically, vasculitis was primary (77.4%) or secondary (22.5%) to drugs, infections, underlying connective tissue diseases and malignancy. Neutrophilic (n=30), lymphocytic (n=18), eosinophilic (n=10), and granulomatous (n=4) vasculitis were the major histopathological groups. Small vessel involvement was seen in 97% cases. Conclusion: Skin biopsy remains the gold standard for diagnosing cutaneous vasculitis. Small vessel vasculitis was the most common type of cutaneous vasculitis with the dominant cell type being neutrophilic. Eosinophilic infiltrate was exclusively associated with primary vasculitis. KEYWORDS: Cutaneous vasculitis; Small vessel vasculitis; Skin biopsy.